SPECIFICS AND PROBLEMS OF EVALUATION OF EFFICIENCY OF INVESTMENT PROJECTS IN MODERN CONDITIONS SPECIFICS - PYLYPIAK, OLEKSANDR; SACHYNSKA, LIUDMYLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The essence of basic indicators for assessing the effectiveness of investment projects in the field of real investment is considered. The basic indicator of the efficiency evaluation system, the discounted payback period, is characterized. The problems of its calculation and limitations of its interpretation are shown. It is shown that this criterion should be used only for the preliminary evaluation of projects with the same life cycle. The basic indicator of the system of efficiency assessment of net present value is characterized. The problems of its calculation and the limitations of its application due to the dependence on the discount rate, which will be different for projects with different levels of risk, are shown. The basic indicator of the system of efficiency evaluation of the internal rate of return is characterized. The problems of its calculation and the limitations imposed on this indicator are shown, especially from the point of view of interpretation. The internal rate of return cannot be used as a full and independent indicator of efficiency. The problems of interpretation of the discounted payback period, net present value, internal rate of return, discounted profitability index in modern conditions and methodological features of the calculation in terms of each indicator and in terms of non-stationary cash flows are highlighted. The advantages and disadvantages of indicators for evaluating the effectiveness of investment projects are shown. Modified indicators of net present value and internal rate of return, which take into account an extremely important factor of reinvestment, are considered separately. The conditions of their application are shown, namely the possibility to receive additional income from reinvestment. In today’s development, this factor is difficult to overestimate. A comparison of net present value and internal rate of return is made using Fisher’s points. Possibilities of their application are shown. The approach to the choice of the criterion for evaluating the effectiveness of investment projects in the field of real investment for given conditions, which is based on the scenario approach, is proposed.